Study of the properties and inhibition of the polyamine oxidase enzyme partially purified from the fruit of green pepper by amyloride and medovi - Wathba Touhala (مجلة التربية والعلم, 2013)
ABSTRACT The study included a detection of PAO in green pepper (Capsicum grossum) and its partial purification by using dialysis and anion exchange chromatography (using DEAE – cellulose) techniques . Two isoenzymes were obtained, with a specific activity of 3.9 and 2.6 unit / mg protein, and a purification fold of 21.4 and 14.3 respectively compared to crude enzyme. Copper ion in both isoenzymes was detected and found to be 0.1915 and 0.2947 mg / ml respectively. The maximum PAOI,II isoenzyme activity were obtained at 100 microlitre of enzyme, sodium phosphate buffer at pH 8.6,7.2, temperature at 40, 37°C, and 125 , 100 mM of spermidine as substrate respectively, and have a high specificity toward the polyamine, spermidine compared with other amine compounds.      The inhibitory effect of the drugs amiloride and medovire on PAOI activity was studied and showed that increasing of inhibitor concentration led to a decrease in activity. The inhibition type was found to be competitive , and Ki were 0.88 and 1.1 mM respectively.           Spermine was detected by HPLC technique from non-proteinous extract. Basic amino acids were  isolated by using  Amberlite 120 H+ and Amberlite 50NH4+ successively, the results indicated that the green pepper contained 96.1  mg / g of plant.